DIGITAL TRANSFORMATION OF STUDENT ENROLLMENT: BUILDING A ROBUST SPMB SYSTEM FOR SMPN 1 YOSOWILANGUN WITH LARAVEL AND WATERFALL APPROACH - Alvionitha Sari Agstriningtyas; Muhammad Ifan; Aisa Dwi Yana; Bima Wijaya (Yayasan Nuraini Ibrahim Mandiri, 2025)
In today’s digital era, educational institutions are increasingly adopting web-based systems to enhance the efficiency and transparency of student admissions. However, many smaller schools in Indonesia still rely on manual admission processes, which are prone to errors, inefficiencies, and lack of transparency. This study aims to address these challenges by developing a New Student Admission Information System (SPMB) for SMPN 1 Yosowilangun using the Waterfall development model and Laravel framework. The system includes core features such as online registration, digital document uploads, automated verification, data management, and an objective selection process. The development process follows five stages of the Waterfall model: requirement analysis, design, implementation, verification, and maintenance. The results show that the system significantly streamlines the admission process, reduces administrative workload, and improves accuracy and user satisfaction. This study provides valuable insights into how small-scale schools can benefit from digital transformation through structured development and appropriate technology.